STUDENTS’ COMMUNICATION STRATEGIES AND TEACHER’S RESPONSES IN A TWELFTH GRADE ENGLISH CLASSROOM IN PALANGKARAYA - Ribka Rayanti Julianny; Josefa J. Mardijono (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
This study is about communication strategies used by the students of twelfth grade and teacher’s responses when they were having an integrated English class. The writer used Mariani’s (2010) theory. The subjecs of the study were 19 students and 1 teacher. The source of data was the students’ and teacher’s utterances during the two meetings. The data were the students’ and teacher’s utterances, (verbal and non-verbal (gestures, eye contact, facial expressions)) which contain communication strategies related to the topic learning. The findings of this study revealed that students used four types of Communication Strategies: Meaning-expression, Meaning-negotiation, Conversation-management and Para- and extra linguistic. The students used these strategies mostly because they were unsure how to answer the teacher’s question and did not know the meaning of the word. The writer hopes that there would be a further study which focused about conversation or speaking class.